Розв’язнiсть оберненої задачi для параболiчного рiвняння з невiдомим молодшим коефiцiєнтом в областi з вiльною межею - Снiтко, Г.А. (Видавничий дім "Академперіодика" НАН України, 2008)
We established the conditions of existence and uniqueness of a solution to the inverse problem for a one-dimensional parabolic equation with unknown time dependent minor coefficient in a domain with free boundary.